Pembrolizumab plus pomalidomide and dexamethasone for patients with relapsed or refractory multiple myeloma (KEYNOTE-183): a randomised, open-label, phase 3 trial. Issue 9 (September 2019) - Mateos, Maria-Victoria; Blacklock, Hilary; Schjesvold, Fredrik; Oriol, Albert; Simpson, David; George, Anupkumar; Goldschmidt, Hartmut; Larocca, Alessandra; Chanan-Khan, Asher; Sherbenou, Daniel; Avivi, Irit; Benyamini, Noam; et al.
Summary: Background: Pomalidomide and dexamethasone is a standard of care for patients with multiple myeloma in whom bortezomib and lenalidomide treatment has failed. KEYNOTE-183 assessed efficacy and safety of pomalidomide and dexamethasone with or without pembrolizumab in patients with relapsed or refractory multiple myeloma. Here, we present the findings of an unplanned, ad-hoc interim analysis at the request of the US Food and Drug Administration (FDA). Methods: KEYNOTE-183 was a randomised, open-label, phase 3 trial done at 97 medical centres across 11 countries (Australia, Canada, France, Germany, Israel, Italy, Japan, New Zealand, Norway, Spain, and USA). Patients aged at least 18 years with multiple myeloma, an Eastern Cooperative Oncology Group (ECOG) performance status 0 or 1, previously treated with at least two lines of therapy (excluding pomalidomide) and refractory to the last line were randomly assigned 1:1 to the pembrolizumab plus pomalidomide and dexamethasone group or the pomalidomide and dexamethasone group via an interactive voice response or integrated web response system. Patients received oral pomalidomide 4 mg daily on days 1–21 and oral low-dose dexamethasone 40 mg on days 1, 8, 15, and 22 in 28-day cycles, with or without intravenous pembrolizumab 200 mg every 3 weeks. The dual primary endpoints were progression-free survival and overall survival. Efficacy was assessed in all randomly assigned patients and safety was assessed in patients who received at least one dose of study treatment. The trial is registered atClinicalTrials.gov, numberNCT02576977, and it is closed for accrual. Findings: Between Jan 18, 2016, and June 7, 2017, 249 patients were randomly assigned to either the pembrolizumab plus pomalidomide and dexamethasone group (n=125) or the pomalidomide and dexamethasone group (n=124). On July 3, 2017, the FDA established that risks associated with the triple combination outweighed benefits and halted the study. Median follow-up was 8·1 months (IQR 4·5–10·9). Median progression-free survival was 5·6 months (95% CI 3·7–7·5) in the pembrolizumab plus pomalidomide and dexamethasone group versus 8·4 months (5·9–not reached) in the pomalidomide and dexamethasone group; progression-free survival estimates at 6 months were 48% (95% CI 37–58) versus 60% (49–69) at 6 months (hazard ratio [HR] 1·53; 95% CI 1·05–2·22; p=0·98). Median overall survival was not reached (95% CI 12·9–not reached) versus 15·2 months (12·7–not reached; HR 1·61; 95% CI 0·91–2·85; p=0·95); overall survival estimates at 6 months were 82% (95% CI 74–88) versus 90% (82–95). Serious adverse events occurred in 75 (63%) of 120 patients in the pembrolizumab plus pomalidomide and dexamethasone group versus 56 (46%) of 121 patients in the pomalidomide and dexamethasone group. Four (3%) treatment-related deaths occurred in the pembrolizumab plus pomalidomide and dexamethasone group (one each of unknown cause, neutropenic sepsis, myocarditis, and Stevens–Johnson syndrome); myocarditis and Stevens-Johnson syndrome were considered related to pembrolizumab. No treatment-related deaths were reported in the pomalidomide and dexamethasone group. Interpretation: The results from this unplanned, FDA-requested, interim analysis showed that the benefit–risk profile of pembrolizumab plus pomalidomide and dexamethasone is unfavourable for patients with relapsed or refractory multiple myeloma. Funding: Merck Sharp & Dohme, a subsidiary of Merck & Co (Kenilworth, NJ, USA).